CURRENT CONSIDERATIONS ABOUT DOPING (Fiep Bulletin - online, 2014)
The content that will be approached in the present task has the objective of showing the several forms and doping types (something that became quite polemic in the sporting world in the last times), the substances that are allowed or forbidden, the consequences of its eventual use, and the swindles that the athletes do to obtain an advantage on its opponent. Some of those methods usually commit the athletes' health. The constant looks for great results that athletes and coaches use several forms for the improvement of the performance, sometimes leaving the sporting ethics sideways and using illicit substances, that is to say, substances rejected by the sport entities.
Keywords: Frauds; illicit substances; health